Strategies to improve teacher competence in elementary schools through information technology-based learning - Hafsah; Ismail; Usman, Nasir; Murniati; Fajri, Munawar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2026)
This study aims to explain IT Training for teachers, the availability of adequate facilities and infrastructure, and Structural support from the school. This study uses a descriptive qualitative approach to map the competencies of elementary school teachers in information technology. Primary data in this study were obtained through observations in schools and through internet searches (Google). This research was conducted at SDN 2 Sampoiniet. The population used in this study totaled 10 (ten) people, consisting of the principal and teachers. The object of this research is Information Technology-Based Learning. Data analysis techniques using the Miles and Huberman approach, which consists of three steps: (1) presenting findings, (2) describing patterns and trends, and (3) understanding the underlying meaning. The research results show that improving teacher competence in Elementary Schools is crucial. Improving teacher competence cannot be done carelessly. A sustainable strategy is needed, such as training programs that focus on using technology in education, professional development, and teacher collaboration. Access to digital resources and institutional support is also very important for ensuring that teachers can adapt to change and use technology to the fullest.